2017
DOI: 10.1111/jocn.13865
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and pharmacy students’ use of emotionally intelligent behaviours to manage challenging interpersonal situations with staff during clinical placement: A qualitative study

Abstract: Students and staff are frequently exposed to stressful clinical environments and challenging interpersonal encounters within healthcare settings. Use of emotionally intelligent behaviours to recognise and effectively manage these encounters may contribute to greater stress tolerance and enhanced professional relationships. Nursing and pharmacy students, and their qualified counterparts, need to be educated to strengthen their emotional intelligence skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…Also, it was mentioned that there was a significant increase in managing self and other emotions with students in high academic year, this is because of the emotional balance as a result of exposing to stressful situations which enable them to handle it more flexible, supportive and planned [10]. In the same line, it was concluded that emotional intelligent behaviors are effective to manage stressful interpersonal interactions [11]. This is in contrast with another research which stated that emotional intelligence was not a useful indicator of performance [12].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was mentioned that there was a significant increase in managing self and other emotions with students in high academic year, this is because of the emotional balance as a result of exposing to stressful situations which enable them to handle it more flexible, supportive and planned [10]. In the same line, it was concluded that emotional intelligent behaviors are effective to manage stressful interpersonal interactions [11]. This is in contrast with another research which stated that emotional intelligence was not a useful indicator of performance [12].…”
Section: Discussionmentioning
confidence: 99%
“…The demographic composition of the sample in which women (91.3%) predominated offers a partial explanation for the high scores recorded across the resilience and performance instruments. Current evidence suggests that female gender is associated with better performance outcomes, particularly in practice education settings (Kanno & Koeske, ; McCloughen & Foster, ). Female occupational therapy students are reported to be more highly motivated and confident at meeting personal challenges and adept at using concentrated periods of practice education to maximise opportunities to develop their relational and reasoning skills (Seah et al, ; Watson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Work‐related stressors across a wide range of health professions, including physiotherapy, social work, pharmacy, dietetics and medicine demonstrate evidence of a spectrum of resilience indicators, including job satisfaction, emotional competence, empathy and tenacity (da Silva Sousa & de Araujo, ). Investigations of social work students on placement highlight the influence of emotional intelligence and levels of supervision on practice education outcomes, whereas medicine and nursing research suggests that personality type, opportunities to discuss difficult clinical events and levels of self‐awareness can impact students’ professional performance and preparation (Houpy, Lee, Woodruff, & Pincavage, ; Kanno & Koeske, ; McCloughen & Foster, ; Skodova, Lajciakova, & Banovcinova, ). Studies from occupational therapy cite the significance of learning styles grade point average, inspirational supervisors, interpersonal skills and academic integrity as contributing factors in practice education performance (Brown et al, ; Yu, Brown, White, Marston, & Thyer, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, results signal Risk Aware's capacity to contribute to healthcare education and training. Placement risk impacts both trainees (Birks et al, ; McCloughen & Foster, ) and professional healthcare workers (Mayhew, ; McDiarmid, ), calling for a move towards improved risk management training (Beech & Leather, ). Given preliminary evidence of Risk Aware's effectiveness in its pilot phase, further investigation of its use in diverse settings is warranted.…”
Section: Discussionmentioning
confidence: 99%